2013
DOI: 10.5586/am.2013.008
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity of yeast-like fungi in some eutrophic lakes in Olsztyn

Abstract: The study is part of hydromycological investigations of man-affected water bodies in Olsztyn. Our results show that yeast-like fungi are permanent components in three selected lakes (lakes Tursko, Długie and Skanda). Their abundance and species composition depend on the trophic state of each lake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Microfungi that have been reported in water for many years , yet are equally important to human health as bacteria, are discounted in routine microbiological diagnostics. Studies by Biedunkiewicz et al conducted in lake pools in Szczecin and its surroundings, in Olsztyn and in an urban water main in Olsztyn confirm the necessity to use fungi as indicators, not only of water purity, but also as bioindicators of potential sanitary and epidemiological hazards . It is undisputed that yeast‐like fungi found in recreational waters may be harmful to human health .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfungi that have been reported in water for many years , yet are equally important to human health as bacteria, are discounted in routine microbiological diagnostics. Studies by Biedunkiewicz et al conducted in lake pools in Szczecin and its surroundings, in Olsztyn and in an urban water main in Olsztyn confirm the necessity to use fungi as indicators, not only of water purity, but also as bioindicators of potential sanitary and epidemiological hazards . It is undisputed that yeast‐like fungi found in recreational waters may be harmful to human health .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since the 1970s, C. albicans has been used as a good indicator of municipal water contamination in monitoring studies in the USA and Canada . However, despite almost 40 years of experience in using C. albicans for water quality evaluation and a number of studies carried out in Poland since the 1980s on bioindicative properties of this species, no calculable effects have been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Aureobasidium also called yeasts-like fungi or black yeasts due to they able to change color become blackish which formerly it was white, cream, light pink, or light brown colony (Chi et al, 2009). Actually, they occur in usual or extreme condition such presence in absolute anaerobes substrate (Biedunkiewicz et al, 2013). Also Babic et al (2016) reported that yeast and yeast-like can be found in house hold appliances.…”
Section: Identification and Phylogenetic Analysismentioning
confidence: 99%
“…In recent years, it has been observed that both developmental forms are detected in samples from different ecosystems. Furthermore, their presence in healthy individuals -asymptomatic carriers and in diseased persons (Cierech et al, 2012) cannot be excluded, which may result in their occurrence in waters used for recreational purposes Biedunkiewicz et al, 2013;. When assessing the purity of waters for their bathing suitability, the presence of fungi poses a significant epidemiological risk.…”
Section: Legend: I -Lake Ii -Swimming Pool Iii -Jacuzzi Iv -Drinkimentioning
confidence: 99%
“…The presence of fungi, especially yeast-like, in different types of water is welldocumented Biedunkiewicz, 2011;Biedunkiewicz and Schulz, 2012;Biedunkiewicz et al, 2013). Many authors have evaluated diverse aspects of purity in freshwater (Wurzbacher et al, 2010), seawater (Vogel et al, 2007), surface waters (Parveen et al, 2011) and across the whole water profile (Bis et al, 2013;Shearer et al, 2007), in outdoor Vogel et al, 2007) and indoor baths (Rasti et al, 2012), in drinking water (Biedunkiewicz and Schulz, 2012) and even in municipal fountains (Biedunkiewicz, 2009).…”
Section: Introductionmentioning
confidence: 99%